First measurements of ocean and atmosphere in the Tropical North Atlantic using Caravela, a novel uncrewed surface vessel. (30th May 2021) - Siddle, Elizabeth; Heywood, Karen J.; Webber, Benjamin G. M.; Bromley, Peter
Abstract : A novel uncrewed surface vessel, an AutoNaut, was deployed from January to March 2020 from Barbados to take part in the Eurec4a campaign, collecting measurements of atmospheric and oceanic conditions to determine surface heat fluxes. This campaign brought together oceanographers and meteorologists to investigate the role of clouds in the Tropical North Atlantic and how they contribute to climate change feedback. This article describes the AutoNaut vessel and preliminary data obtained during Eurec4a.